(untitled) (Research, Society and Development, 2021)
Cassava root rot causes significant production losses. Difficulties of management, along with the lack of chemical fungicides officially registered by the Ministry of Agriculture, Livestock and Supply (MAPA), require alternative control methods. This study investigated the in vitro antagonistic activity of Trichoderma harzianum as well as a biological fertilizer MICROGEO® on Fusarium solani. The phytophatogenic strains of F. solani, called F1 and F2 were isolated from rotted cassava tubers and T. harzianum, strain ESALQ 1306, from a biological fungicide. Continuous liquid composting of bovine ruminal content, water and MICROGEO® produced the biological fertilizer. Dual culture method was used at the bioassay with T. harzianum. Sterilized (St) and unsterilized (USt) biological fertilizer were tested in different concentrations (% v/v) diluted in the culture media. Colony diameters were measured daily in order to establish the mycelial growth velocity index, inhibition percentage, aside from the sporulation rate and spore germination percentage. The mycelial growth of F. solani isolates was interrupted after hyphae encounter with T. harzianum, due to the occurrence of mycoparasitism, but without influence on the sporulation rate. Sterilized biological fertilizer induced no biocontrol, whereas the unsterilized product (concentration 2.5%) inhibited approximately 64% and 85% of the mycelial growth of isolates F1 and F2, respectively. Moreover, spore germination declined with increasing concentration. In conclusion, T. harzianum and the unsterilized biofertilizer showed in vitro antagonistic activity on F. solani.